Fostering Transformation by Hearing Voices: Evaluating a 6-Second, Low-Fidelity Simulation. (September 2018) - Marshall, Brenda; Bliss, Julie; Evans, Benjamin; Dukhan, Oksana
BACKGROUND: The stigma of psychosis, with the accompanying symptoms of auditory and visual hallucinations, can affect a nurse's ability to provide safe, effective care. Increasing knowledge of the patient's perspective during auditory hallucinations can increase the nurse's ability to be empathetic and engage in a therapeutic alliance.OBJECTIVE: To evaluate the efficacy of a six-second auditory hallucination simulation to increase empathy in preclinical undergraduate nursing students.DESIGN: This descriptive, content analysis, qualitative study evaluated narratives written by students in a pre-licensure baccalaureate nursing student population, assessing empathy, insight, knowledge, and therapeutic communication. Students experienced the 6-second auditory hallucination simulation as part of preclinical instruction, and then they wrote a self-reflection.RESULTS: More than 200 self-reflections were collected, with a randomized final sample of 82 narratives evaluated.CONCLUSION: Self-reflections indicated that the experience of the 6-second hearing voices simulation increased efficacy, insight, knowledge, and intention to use therapeutic communication.